AN ANALYSIS OF SPELLING ERRORS ON FACEBOOK POSTS - Claudy Three An Calla Claudy; Eusabinus Bunau Bunau; Wardah Wardah (LPPM Universitas PGRI Jombang, 2024)
This study aims to identify the types of spelling errors in Facebook posts. In this research, there were four categories of spelling errors used such as addition, omission, substitution and ordering. In addition, the research object used was types of a random Facebook posts on group English Learning such as text status updates, comment posts, and photo posts and that consisted of thirty posts as the object of this research. This study used a descriptive-qualitative method. It can be concluded from the result of this research that the dominant spelling errors found was omission. In addition, other classifications of spelling errors also found were addition, substitution, and ordering.